(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article today, the focus is on the student, his personality and unique inner world. Therefore, the main goal of a modern teacher is to choose methods and forms of organizing students whose educational activities are optimally compatible with the goal of personality development. In recent years, the issue of using new information technologies in schools has been increasingly raised.